2015
DOI: 10.1117/12.2178392
|View full text |Cite
|
Sign up to set email alerts
|

Defect luminescence in oxides nanocrystals grown by laser assisted techniques

Abstract: Wide band gap oxides, such as ZnO, SnO 2 and ZrO 2 , are functional materials with a wide range of applications in several important technological areas such as those including lighting, transparent electronics, sensors, catalysis and biolabeling. Recently, doping and co-doping of oxides with lanthanides have attracted a strong interest for lighting purposes, especially among them nanophosphors for bioassays. Tailoring the crystalline materials physical properties for such applications often requires a well-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…It has been reported that photocatalytic performance of semiconductors can be improved by doping with certain cations, which can act as electron trapping agent to decrease the electron-hole recombination rate. [9,10,11] The photocatalytic activity of ZnO can be significantly enhanced by doping with the lanthanide ions having 4f configuration, among them, cerium-doped ZnO nanomaterials exhibited versatile properties and much attention has been focused to explore them for possible applications in various technologies. [12,13] Doping RE ions into ZnO produces a significant improvement in the charge separation between photogenerated electrons and holes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that photocatalytic performance of semiconductors can be improved by doping with certain cations, which can act as electron trapping agent to decrease the electron-hole recombination rate. [9,10,11] The photocatalytic activity of ZnO can be significantly enhanced by doping with the lanthanide ions having 4f configuration, among them, cerium-doped ZnO nanomaterials exhibited versatile properties and much attention has been focused to explore them for possible applications in various technologies. [12,13] Doping RE ions into ZnO produces a significant improvement in the charge separation between photogenerated electrons and holes.…”
Section: Introductionmentioning
confidence: 99%